(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Cadmium (Cd) is known to affect reproductive functions adversely. Carpolobia lutea is a protective herbal derivative due to its antioxidant potential. This study investigates the steroidogenic activities of methanol extract of Carpolobia lutea root on cadmium-induced reproductive toxicity in male Wistar rats. Carpolobia lutea root was obtained in Ijare via Akure. The plant was authenticated at the herbarium of Forestry Research Institute of Nigeria (FRIN), Ibadan, Nigeria, with FHI number 109784. The methanol extract Carpolobia lutea root (MCL) was obtained by Soxhlet extraction. Thirty male Wistar rats (150-170g) were used in this study (n=5) and treated as follows: Control, Cd (2 mg/kg), Cd+MCL (2 mg/kg+100 mg/kg), Cd+MCL (2 mg/kg+200 mg/kg), MCL (100 mg/kg), and MCL (200 mg/kg). The extract was administered orally for eight weeks, and a single dose of 2 mg/kg Cd was given intraperitoneally. Serum Follicle Stimulating Hormone (FSH), Luteinizing hormone (LH), testosterone levels, testicular hydroxysteroid dehydrogenases (HSDs) activities and Steroidogenic Acute Regulatory protein (StAR) expression were evaluated. Data were subjected to descriptive statistics and analysed using ANOVA at p<0.05. Serum FSH, LH, testosterone levels, 3β-HSD, 17β-HSD activities and StAR expression were significantly reduced (p<0.05) in Cd group. The co-administration of Cd with MCL (200mg/kg) significantly increased (p<0.05) serum FSH, LH, testosterone levels, 3β-HSD, 17β-HSD activities and StAR expression when compared with Cd group. Carpolobia lutea root extract improved steroidogenic activity in male Wistar rats exposed to cadmium.